Incomplete Information, Risk Shifting, and Employment Fluctuations - Grossman, Herschel I. (Review of Economic Studies, 1981)
Journal Article Incomplete Information, Risk Shifting, and Employment Fluctuations Get access Herschel I. Grossman Herschel I. Grossman Brown University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 2, April 1981, Pages 189–197, https://doi.org/10.2307/2296879 Published: 01 April 1981 Article history Received: 01 March 1980 Accepted: 01 October 1980 Published: 01 April 1981